Recent developments in the realistic geometric modelling of textile structures using TexGen - Brown, Louise P.; Zeng, Xuesen; Long, Andrew.C.; Jones, I. Arthur (2013)
Realistic geometric representation of fabrics is essential for modelling of mechanical and physical properties of textiles and textile composites. It is also advantageous to be able to generate those models quickly and easily. Recent developments in TexGen which automate the creation of models for 3D orthogonal, angle interlock and layer-to-layer fabrics and sheared 2D fabrics are described. Micro-Computed Tomography data of 3D fabrics has been used to identify geometrical characteristics which have formed the basis for implementation of refinements to the idealised fabrics generated automatically in TexGen. In 3D orthogonal textiles local geometrical variations, particularly in yarn cross-section, surface crimp and binder yarn path are apparent at different levels of compaction. The “refine” option in TexGen‟s 3D wizard automatically adjusts these features to achieve compaction to a specified thickness, using yarn volume fraction as a constraint. For sheared textiles a generic 2D plain weave fabric was used to identify key geometric features. Yarn rotation has been identified as one of these and the geometric description of the sheared fabric considers yarn rotations in terms of two elliptical cylinders crossing each other at an oblique angle. The rotational angle is derived mathematically from the tangential contact between yarns. Variations in yarn height along the length of the yarn have also been identified and both of these features are incorporated into a refine function for sheared textiles. Compatible voxelised mesh and periodic boundary conditions for the sheared domain have also been implemented. The models have been used to generate manufacturing data: permeability data for the 3D fabric and coefficient of thermal expansion for the sheared 2D fabric.